2018
DOI: 10.5815/ijwmt.2018.02.01
|View full text |Cite
|
Sign up to set email alerts
|

High-reliability Vehicle Detection and Lane Collision Warning System

Abstract: In the last two decades, developing Driving Assistance Systems for security has been one of the most active research fields in order to minimize traffic accidents. Vehicle detection is a vital operation in most of these applications. In this paper, we present a high reliable and real-time lighting-invariant lane collision warning system. We implement a novel real-time vehicles detection using Histogram of Oriented Gradient and Support Vector Machine which could be used for collision prediction. Thus, in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The drone is able to automatically decrease the vibration, although inevitable rotation still exists, due to wind in the sky. Deep learning methods were often used when performing vehicle detection and classification [28,29]. In this study, the trajectory generation workflow was shown in Figure 1, combing several deep learning methods.…”
Section: Methodsmentioning
confidence: 99%
“…The drone is able to automatically decrease the vibration, although inevitable rotation still exists, due to wind in the sky. Deep learning methods were often used when performing vehicle detection and classification [28,29]. In this study, the trajectory generation workflow was shown in Figure 1, combing several deep learning methods.…”
Section: Methodsmentioning
confidence: 99%